Real-Time Video Feedback Training to Improve Tennis Serve Accuracy and Biomechanics in Junior Players - Ians Aprilo; Poppy Elisano Arfanda; M. Adam Mappaompo; Yasriuddin; Hasby Asyhari (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effect of real-time video feedback on improving serve accuracy and movement biomechanics in junior tennis athletes. The study used a quantitative approach with a pre-test–post-test control group design. The study sample consisted of 20 junior tennis athletes aged 14–16 years in Makassar City who were divided into an experimental group and a control group. Data were collected through the Hewitt Serve Test, biomechanical observations, and video documentation analyzed using Kinovea software. The experimental group was given real-time video feedback-based training for 8 weeks, while the control group underwent conventional training. Data analysis used a paired sample t-test and Cohen's d at a significance level of α = 0.05. The results showed a significant increase in serve accuracy from 62.4% to 81.7%. In addition, trunk rotation increased by 18%, elbow angle by 12%, and movement timing coordination by 15%. A t-value of 9.21 and Cohen's d of 3.22 indicate that the use of real-time video feedback significantly impacts the quality of junior tennis athletes' service techniques. The implications of this study suggest that the use of real-time video technology can be an effective training strategy to improve technical performance, biomechanical evaluation, and coaching efficiency of young tennis athletes.